Peer Group Education Effective on Students' Anxiety Levels Facing Premenstrual Syndrome - Anastasya Febiyani Bari; Regina Vidya Trias Novita; Ainum J Hidayah (Universitas Aisyah Pringsewu, 2023)
Adolescence in teenage girls, sexual maturity is marked by menstruation. Disorders accompanying menstruation are called Premenstrual Syndrome (PMS). The most common symptoms are crying easily, irritability, difficulty concentrating, and anxiety. The purpose of this research is to analyze the effect of peer group education on the level of PMS anxiety in female students at BHK Grogol High School, West Jakarta. The design of this research is pre-experimental with one group pre-post test design. The population is all students of grades X and XI at SMA BHK Grogol, who are already menstruating with sample 77 students. The technique used is the proportional random. Peer education and independent variables PMS anxiety dependent variable. Data collection using a questionnaire, and statistical test. The paired t-test is used to see the effect of peer group education on the level of students' anxiety about PMS. There was a lot of respondents' anxiety before pre-education categories of no stress, mild anxiety, moderate, severe, and very severe, as many as 29 each (37.7%) 23 (29.9%),16 (20.8%), 8 (10.4%), and 1 (1.3%). Respondents' anxiety after the intervention 56 (72.7%) had no anxiety, 15 (19.5%) had moderate anxiety and 6 (7.8) had anxiety currently. The results of the paired t-test showed a significant value of 0.000 less than 0.05. It can be concluded that there is an effect of peer group education on PMS anxiety in class X and XI students at BHK Grogol High School, West Jakarta.